Timing of Protein/energy Supplementation in Late Gestating Bos Indicus-influenced Beef Cows Influences Postnatal Growth, Immunity and Carcass Characteristics of Their Offspring - Palmer, Elizabeth A (J Anim Sci, 2021)
This 2-yr study investigated the timing of dried distillers grains (DDG) supplementation of Bos indicus-influenced cows during late gestation and its impacts on offspring performance. On d 0, 84 Brangus cows/yr were stratified by BW (482 ± 75 kg) and BCS (5.3 ± 0.8) and randomly assigned to bahiagrass pastures (14 cows/pasture). Treatments were randomly assigned to pastures (2 pastures/treatment/yr) and consisted of no prepartum supplementation (CON), 2 kg/d of DDG from d 0 to 42 (LATE42), or 1 kg/d of DDG from d 0 to 84 (LATE84). At weaning (d 347), 38 steers/yr were vaccinated against bovine respiratory disease, transported for 720 mi to the feedlot, penned according to prepartum pasture distribution, and fed the same corn silage-based diet until harvest. Data were analyzed using SAS GLIMMIX procedure. Cow BCS at calving was greater (P ≤ 0.05) for LATE84 and LATE42 vs. CON cows and did not differ (P = 0.16) between LATE84 and LATE 42 cows. Cows offered LATE42 supplementation had greater (P ≤ 0.05) calving percentage from wk 2 to 6 of the subsequent calving season than CON and LATE84 cows. Calf BW at weaning was greater (P ≤ 0.05) for LATE 84 vs. LATE42 calves, and the latter greater than CON calves (269, 261, and 255 ± 2.6 kg, respectively). Seroconversion against parainfluenza-3 virus at weaning was greater (P ≤ 0.05) for LATE42 vs. CON steers, with LATE84 being intermediate. Feedlot BW and carcass weight did not differ (P ≥ 0.36) among treatments, but marbling scores and carcasses grading choice tended (P ≤ 0.10) to be greater for LATE42 vs. CON steers, with LATE84 being intermediate. Therefore, timing of DDG supplementation during late gestation in Bos indicus-influenced cows enhanced calf weaning weight, humoral immunity, and carcass characteristics at different magnitudes than cohorts born from non-supplemented cows.